Dual Transcriptome and Metabolic Analysis of Vitis vinifera cv. Pinot Noir Berry and Botrytis cinerea During Quiescence and Egressed Infection - Haile, Zeraye Mehari; Malacarne, Giulia; Pilati, Stefania; Sonego, Paolo; Moretto, Marco; Masuero, Domenico; Vrhovsek, Urska; Engelen, Kristof; Baraldi, Elena; Moser, Claudio (Frontiers in Plant Science, 2020)
Botrytis cinerea is an important necrotroph in vineyards. Primary infections are mostly initiated by airborne conidia from overwintered sources around bloom, then the fungus remains quiescent from bloom till maturity and egresses at ripeness. We previously described in detail the process of flower infection and quiescence initiation. Here, we complete the characterization studying the cross-talk between the two organismsplant and the fungus during pathogen quiescence and egression by an integrated transcriptomic and metabolic analysis of the host and the pathogen. Flowers from fruiting cuttings of the cv. Pinot noir were inoculated with a GFP-labeled strain of B. cinerea at full cap-off stage, and molecular analyses were carried out at 4 weeks post inoculation (wpi, fungal quiescent state) and at 12 wpi (fungal pre-egression and egression states). During the quiescent state, tThe expressed fungal transcriptome highlighted that the fungus was remodeling remodels its cell wall to evade plant chitinases besides undergoing basal metabolic activities. Berries responded by differentially regulating genes encoding for different PR proteins and genes involved in monolignol, flavonoid and stilbenoid biosynthesis pathways. At 12 wpi, the transcriptome of B. cinerea in the pre-egressed samples showed that virulence-related genes were expressed, suggesting infection process was initiated. The egressed B. cinerea expressed almost all virulence and growth related genes that enabled the pathogen to colonize the berries. In response to egression, ripe berries reprogrammed different defense responses, though futile. Examples are activation of membrane localized kinases, stilbene synthases and other PR proteins related to SA and JA-mediated responses. Our results indicated that hard-green berries defense program was capable to hamper B. cinerea growth. However, ripening associated fruit cell wall self-disassembly together with high humidity created the opportunity for the fungus to egress and cause bunch rot.